Relevansi Filsafat Pragmatisme William James dalam Membangun Sikap Moderat di Tengah Masyarakat Multireligius : The Relevance of William James's Pragmatist Philosophy in Building a Moderate Attitude in a Multireligious Society - Tembang, Setblon; Prihatini, Hesti Wahyu; Sahrudin, Heru; Sugiarti, Lucia Rini; Suhariadi, Fendy (Jurnal Filsafat Indonesia, 2025)
This research is motivated by the difference between the idealism and reality of religion in life. Religion idealistically teaches about goodness, peace, and love, which is the strength that enables it to encourage its adherents to fight for love, humanity, peace, and unity in humanising humanity. However, in reality, religion has become one of the instruments that trigger violence, both verbally and physically, as well as prolonged conflict. The purpose of this research is to provide an insight into the philosophical foundation from the perspective of William James's pragmatism in developing moderate behaviour in a multicultural society. This research employs a descriptive qualitative approach, grounded in library research. The results of this research indicate that William James's pragmatist philosophy emphasises the utility of religion for humans, specifically in improving their moral character. If it is not beneficial, then it should be left alone. William James's pragmatist philosophy holds that every religion possesses a sacredness derived from the divine, which must be treated with mutual respect and appreciation for existing differences. Religious moderation is a concrete form of religious practice that is moderate in confronting religious radicalism, which threatens the very existence of religion and also impacts social, national, and state life. William James's pragmatic philosophy serves as the philosophical foundation for fostering religious moderation amidst religious pluralism in Indonesia, emphasising the effectiveness of truth that is not merely theoretical but also real in its application. Therefore, religious individuals must practice their faith wisely and express their beliefs without relying on extremism and narrow, dogmatic attitudes.